Light Regulation of LHCX Genes in the Benthic Diatom Seminavis robusta - Blommaert, Lander; Vancaester, Emmelien; Huysman, Marie J. J.; Osuna-Cruz, Cristina M.; D’hondt, Sofie; Lavaud, Johann; Lepetit, Bernard; Winge, Per; Bones, Atle M.; Vandepoele, Klaas; Vyverman, Wim; Sabbe, Koen (Frontiers in Marine Science, 2020)
Intertidal benthic diatoms experience a highly variable light regime, which especially challenges these organisms to cope with excess light energy during low tide. Non-photochemical quenching of chlorophyll fluorescence (NPQ) is one of the most rapid mechanisms diatoms possess to dissipate excess energy. Its capacity is mainly defined by the xanthophyll cycle and Light-Harvesting Complex X (LHCX) proteins. Whereas the xanthophyll cycle and its relation to NPQ have been relatively well-studied in both planktonic and benthic diatoms, our current knowledge about LHCX proteins and their potential involvement in NPQ regulation is largely restricted to planktonic diatoms. While recent studies using immuno-blotting have revealed the presence of light regulated LHCX proteins in benthic diatom communities and isolates, nothing is as yet known about the diversity, identity and transcriptional regulation or function of these proteins. We identified LHCX genes in the draft genome of the model benthic diatom Seminavis robusta and followed their transcriptional regulation during a day/night cycle and during exposure to high light conditions. The S. robusta genome contains 17 LHCX sequences, which is much more than in the sequenced planktonic model diatoms (4-5), but similar to the number of LHCX genes in the sea ice associated diatom Fragilariopsis cylindrus. LHCX diversification in both species, however, appears to have occurred independently. Interestingly, the S. robusta genome contains LHCX genes that are related to the LHCX6 of the model centric diatom Thalassiosira pseudonana, which are lacking in the well-studied pennate model diatom Phaeodactylum tricornutum. All investigated LHCX genes, with exception of SrLHCX6, were upregulated during the daily dark-light transition. Exposure to 2000 µmol photons m-2s-1, furthermore, increased transcription of all investigated LHCX genes. Our data suggest that the diversification and involvement of several light regulated LHCX genes in the photophysiology of S. robusta may represent an adaptation to the complex and highly variable light environment in this benthic diatom species.